A Comparative Perspective on Functionally-Related, Intracellular Calcium Channels: The Insect Ryanodine and Inositol 1,4,5-Trisphosphate Receptors - Umut Toprak; Cansu Doğan; Dwayne Hegedus (Biomolecules, 2021)
Calcium (Ca2+) homeostasis is vital for insect development and metabolism, and the endoplasmic reticulum (ER) is a major intracellular reservoir for Ca2+. The inositol 1,4,5- triphosphate receptor (IP3R) and ryanodine receptor (RyR) are large homotetrameric channels associated with the ER and serve as two major actors in ER-derived Ca2+ supply. Most of the knowledge on these receptors derives from mammalian systems that possess three genes for each receptor. These studies have inspired work on synonymous receptors in insects, which encode a single IP3R and RyR. In the current review, we focus on a fundamental, common question: “why do insect cells possess two Ca2+ channel receptors in the ER?”. Through a comparative approach, this review covers the discovery of RyRs and IP3Rs, examines their structures/functions, the pathways that they interact with, and their potential as target sites in pest control. Although insects RyRs and IP3Rs share structural similarities, they are phylogenetically distinct, have their own structural organization, regulatory mechanisms, and expression patterns, which explains their functional distinction. Nevertheless, both have great potential as target sites in pest control, with RyRs currently being targeted by commercial insecticide, the diamides.